OPTIMIZING ISLAMIC RELIGIOUS EDUCATION LEARNING IN ELEMENTARY SCHOOLS THROUGH CONTEXTUAL APPROACH: A LITERATURE REVIEW OF CURRICULUM AND TEACHING METHODS - Nadirah, Sitti; Retoliah, Retoliah; Aniati, Aniati; Idris, Idris; Hisbullah, Hisbullah (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: This article is a literature review aimed at analyzing and explaining the contextual approach in enhancing the effectiveness of Islamic Religious Education (IRE) learning in Elementary Schools (ES). Purpose: The contextual approach is a teaching method that emphasizes the relevance of learning materials to students' daily lives and environments. In the context of IRE, this approach involves connecting Islamic religious lessons with life situations and Islamic values relevant to ES students. Method: Through a comprehensive literature review, this article explores previous studies and research involving the curriculum and teaching methods of IRE in ES using a contextual approach. This literature review covers various aspects, such as comparing the effectiveness between contextual and conventional approaches, their impact on understanding Islamic religion, students' learning interest, and participation in IRE learning. The article also discusses the challenges and opportunities in implementing the contextual approach in IRE learning in ES, including teachers' perspectives, required curriculum changes, and support from the school environment and families. Result: The results of this literature review indicate that the contextual approach can enhance the effectiveness of IRE learning in ES significantly. The relevance of learning materials to students' daily lives motivates them to be more engaged and to better appreciate Islamic values. In conclusion, the contextual approach has the potential to make a positive contribution to the development of IRE learning in ES. Conclusion: This article provide valuable insights for educators, researchers, and policymakers in the field of Islamic education, and encourage more empirical research to support and strengthen the findings of this literature review.